PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIKKELAS VIII SMPN 3 RANAH PESISIR - Selvi Megia (Departemen Matematika, 2022)
Mathematical reasoning ability is very important for students to be able to make decisions or solution in solving various problems in the mathematical context. The purpose of the study was to describe the effect of the Discovery Learning model on students mathematical reasoning abilities better than students mathematical reasoning of students who learn by using direct learning and describe the development of mathematical reasoning abilities of student who study with the Discovery Learning model. The type of research is quasy-experiment and descriptive with a Randomized Control Group Only Design. The research instrument is a test of mathematical reasoning abilities. From the data analysis it was concluded that students' mathematical reasoning abilities that applied the Discovery Learning model were better than the students' mathematical reasoning abilities who applied direct learning in class VIII SMPN 3 Ranah Pesisir. there was an increase in students' mathematical reasoning abilities while learning to apply the Discovery Learning model. The development of mathematical reasing skills by applying Discovery Learning model has increased in each indicator. Keywords – The Ability Of Mathematical Reasoning, Discovery Learning Model, Learning Direct